STRATEGI KAMPANYE POLITIK PARTAI GERINDRA DI MEDIA SOSIAL INSTAGRAM (@Gerindra) PADA PEMILU TAHUN 2019 - Nurul Aulia Mijayanti (2022)
This study departs from the background of the use of digital media in the 2019 Simultaneous Elections to become a moment for political parties to campaign through expressing netizen politics. Including the Gerindra Party, which uses digital media through the Instagram platform to campaign in the 2019 General Election. The Gerindra Party is a political party that is quite active on social media, so the campaigns carried out by the Gerindra Party on social media, especially Instagram social media, are quite active and aggressive. The purpose of this study was to find out how the Gerindra Party's strategy was in conducting campaigns through the Instagram platform in the 2019 Election. The research method used in this study was a qualitative research method. The results of this study found the strategy used by the @Gerindra Instagram account in campaigning on Instagram social media. There are several aspects that affect the success of the @Gerindra account's campaign strategy, such as campaign design, campaign planning, selection of digital media distribution channels, the role of the campaign team or influencers, software use, budgeting, monitoring, populist issues, external media responses when viewing content, what audience interest, audience behavior and segments, and evaluation of campaign content. From the implementation of the Instagram @Gerindra social media campaign strategy, it generates feedback from netizens on every uploaded campaign content. Thus, this made the Gerindra Party win the second vote after PDIP in the voting in the 2019 Election with a total vote of 17,594.839 with a percentage: 12.57%.